Mobile Internet Telephony Improves Speech Intelligibility and Quality for Cochlear Implant Recipients. Issue 3 (March 2019) - Guignard, Jérémie; Senn, Pascal; Koller, Roger; Caversaccio, Marco; Kompis, Martin; Mantokoudis, Georgios
Abstract : Objective: The objective of this study was to investigate the benefit of mobile Voice over Internet protocol (VoIP) over conventional mobile phone calls (Global System for Mobile Communications, GSM) on speech intelligibility and quality for cochlear implant (CI) recipients. Study Design: Cross-sectional, prospective. Setting: Tertiary referral center. Patients: A volunteer sample of experienced, German-speaking, adult CI recipients was considered. Volunteers with less than 50% aided monosyllabic word discrimination were excluded. Intervention: Smartphone communication was changed from GSM to VoIP on two separate devices (A and B). Main Outcome Measures: Speech intelligibility was assessed with the Hochmair-Shulz-Moser (HSM) test in noise, speech quality with the mean opinion score (MOS) survey and the perceptual evaluation of speech quality (PESQ) algorithm. Results: With device A, the mean HSM scores were 64.40% ± 32.41 with GSM and 77.28% ± 21.60 with VoIP ( p = 0.0573). 66.7% of patients had a higher score with VoIP. For device B the means were 53.90% ± 21.77 and 69.07% ± 21.09 ( p < 0.0001). 94.1% patients scored better with VoIP. With device A the average MOS scores were 3.12 ± 1.52 and 4.08 ± 0.95 ( p = 0.0078). 76.9% of patients gave a higher score with VoIP. With device B the means were 2.71 ± 1.08 and 3.528 ± 1.44 ( p = 0.0068). 56.3% of patients gave a higher score with VoIP. The effect was smaller when using an accessory cable. PESQ scores were significantly higher with VoIP ( p < 0.001) in all configurations. Conclusions: CI recipients experience speech intelligibility and quality improvements using VoIP on a smartphone compared with conventional mobile phone calls.